Novel solvates M(BH4)3S(CH3)2 and properties of halide-free M(BH4)3 (M = Y or Gd) - Ley, M.; Paskevicius, Mark; Schouwink, P.; Richter, B.; Sheppard, Drew; Buckley, Craig; Jensen, T. (R S C Publications, 2014)
Rare earth metal borohydrides have been proposed as materials for solid-state hydrogen storage because of their reasonably low temperature of decomposition. New synthesis methods, which provide halide-free yttrium and gadolinium borohydride, are presented using dimethyl sulfide and new solvates as intermediates. The solvates M(BH4)3S(CH3)2 (M = Y or Gd) are transformed to a-Y(BH4)3 or Gd(BH4)3 at ~140 °C as verified by thermal analysis. The monoclinic structure of Y(BH4)3S(CH3)2, space group P21/c, a = 5.52621(8), b = 22.3255(3), c = 8.0626(1) Å and ß = 100.408(1)°, is solved from synchrotron radiation powder X-ray diffraction data and consists of buckled layers of slightly distorted octahedrons of yttrium atoms coordinated to five borohydride groups and one dimethyl sulfide group. Significant hydrogen loss is observed from Y(BH4)3 below 300 °C and rehydrogenation at 300 °C and p(H2) = 1550 bar does not result in the reformation of Y(BH4)3, but instead yields YH3. Moreover, composites systems Y(BH4)3–LiBH4 1 : 1 and Y(BH4)3–LiCl 1 : 1 prepared from as-synthesised Y(BH4)3 are shown to melt at 190 and 220 °C, respectively.